Advances in synthesis gas methods, technologies and applications - Makarem, Mohammad Amin; Meshksar, Maryam; Rahimpour, Mohammad Reza (Elsevier, 2023)
"Advances in Synthesis Gas: Methods, Technologies and Applications: Syngas Products and Usage considers the applications and usages of syngas for producing different chemical materials such as hydrogen, methanol, ethanol, methane, ammonia, and more. In addition, power generation in fuel cells, or in combination with heat from syngas, as well as iron reduction with economic and environmental challenges for syngas utilization are described in detail."